The professional practice of architectural working drawings - Wakita, Osamu A.; Bakhoum, Nagy R.; Linde, Richard M. (Wiley, 2024)
"The Professional Practice of Architectural Working Drawings presents the complete range of skills and principles needed to create a set of professional architectural working drawings. In a logical progression that mimics an architect's workflow, the content covers everything from site and foundation plans to building sections and elevations. Hundreds of drawings illustrate each step in the process, using both residential and light commercial projects as examples. Computer-generated drawings, including BIM and 3D models, show how the principles covered in the book can be applied to the latest architectural technologies. The Fifth Edition includes revised coverage of sustainability and its affect on working drawings, updated layering systems that are in line with AIA standards, in-depth explanations of dimensioning, a new selection of case studies, and more samples of ADA project drawings. It also includes access to a robust set on online ancillary materials for students and instructors"--